Equatorial Atlantic hydrographic and seawater sensor data collected during RRS James Cook cruise JC094: dive 225 - Laura F Robinson (PANGAEA, 2022)
This data release includes sensor data collected from Remotely Operated Vehicle (ROV) sensors during a 2013 (October - November) research expedition onboard the RRS James Cook, JC094, in the Equatorial Atlantic Ocean. The JC094 TROPICS cruise was a fieldwork component of a European Research Council funded project, CACH ( extquotesingleReconstructing abrupt Changes in Chemistry and Circulation of the Equatorial Atlantic Ocean: Implications for global Climate and deep-water Habitats extquotesingle) led by Prof. Laura Robinson from the University of Bristol to study paleoclimate archives in the Atlantic. Seventeen ROV dives were carried out. All data have been binned by time.
In: Robinson, LF (2022): Equatorial Atlantic hydrographic and seawater sensor data collected during RRS James Cook cruise JC094 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.952691